p16 is Consistently Expressed in Endometrial Tubal Metaplasia - N. Horree; A. P. M. Heintz; D. M. D. S. Sie-Go; P.J. van Diest (Cellular Oncology)
Background: Cell cycle proteins and HIF-1α with downstream factors are often abberrantly expressed in (pre)neoplastic tissue. Methods: Paraffin-embedded specimens of inactive endometrium with TM (n=15), ovarian inclusion cysts (n=6), cervix with TM (tubal metaplasia) (n=3), Fallopian tubes (n=7), cycling endometrium (n=9) and a ciliated cell tumor of the ovary were stained for p16 and LhS28. 39 Endometrioid endometrial carcinomas and 5 serous endometrial carcinomas were stained for p16. Additionally, inactive endometrium (n=15) was immunohistochemically stained for p21, p27, p53, cyclin A, cyclin D1, cyclin E, HIF-1α, CAIX, Glut-1 and MIB-1. Results: A mosaic pattern of expression of p16 was seen throughout in all cases of endometrial TM (15/15), in 2/6 of the ovarian inclusion cysts with TM, in all (3/3) cervical TM and focal in 5/7 of Fallopian tube cases. Mosaic expression was also seen in a ciliated cell tumor of the ovary and in 18/39 of endometrioid endometrial carcinomas, and diffuse p16 expression was seen in 5/5 serous carcinomas. In comparison with normal endometrium, TM areas in the endometrium showed significantly increased expression of HIF-1α, cyclin E, p21 and cyclin A, and decreased expression of p27. Membranous expression of CAIX and Glut-1 was only seen in TM areas, pointing to functional HIF-1α. Conclusion: As p16 is consistently expressed in TM, less and only patchy expressed in the normal Fallopian tube, is paralleled by aberrant expression of cell cycle proteins, HIF-1α, CAIX and Glut-1 and resembles the pattern of p16 expression frequently seen in endometrial carcinomas, we propose endometrial TM to be a potential premalignant endometrial lesion.